Human immune system: Exploring diversity across individuals and populations - Kim Han Hoang Nguyen; Nghi Vinh Le; Phuc Hoang Nguyen; Hien Hau Thi Nguyen; Duy Mai Hoang; Chien Dinh Huynh (Heliyon)
The immune response is an intricate system that involves the complex connection of cellular and molecular components, each with distinct functional specialisations. It has a distinct capacity to adjust and mould the immune response in accordance with specific stimuli, influenced by both genetic and environmental factors. The presence of genetic diversity, particularly across different ethnic and racial groups, significantly contributes to the impact of incidence of diseases, disease susceptibility, autoimmune disorders, and cancer risks in specific regions and certain populations. Environmental factors, including geography and socioeconomic status, further modulate the variety of the immune system responses. These, in turn, affect the susceptibility to infectious diseases and development of autoimmune disorders. Despite the complexity of the relationship, there remains a gap in understanding the specificity of immune indices across races, immune reference ranges among populations, highlighting the need for deeper understanding of immune diversity for personalized approaches in diagnostics and therapeutics. This review systematically organizes these findings, with the goal of emphasizing the potential of targeted interventions to address health disparities and advance translational research, enabling a more comprehensive strategy. This approach promises significant advancements in identifying specific immunological conditions, focusing on personalized interventions, through both genetic and environmental factors.